Idol Attachment and Human Brand Loyalty - Huang, Y.; Lin, Chad; Phau, Ian (Emerald, 2015)
Purpose: This paper examines the importance and concept of idol attachment, models its antecedents and moderators, and assesses its influence on human brand loyalty. Design/methodology/approach: This paper includes two studies. In study 1, survey questionnaires were distributed by mall intercept to quasi-random samples across Australia and Taiwan for completion and return. The return yielded 1135 and 736 usable questionnaires, respectively, the data from which were analysed using LISREL structural equation modelling software. In study 2, an experiment was employed to examine whether idol attractiveness is likely to positively moderate the relationship between vanity traits and attachment. Findings: The results suggest that achievement vanity, variety seeking, and peer norms have a positive impact on the phenomenon of idol attachment, which in turn positively affects human brand loyalty. Contradicting previous studies, the physical appearance of vanity was not found to be associated with idol attachment. However, the results of the experiment show idol attractiveness has a positive moderating effect on the relationship between vanity traits and human brand attachment. Research limitations/implications: The findings suggest that idol attachment is more complex than previously understood. The constructs chosen in this research represent an initial step but other variables such as liking, involvement, affective commitment, and brand love are not taken into account. Future research models should therefore include such variables. Practical implications: The findings contain many practical lessons for planners of marketing strategy for the music industry in an international context. Originality/value: Two existing theories of psychology are integrated with the concept of idol attachment to explain human brand loyalty in an international context.